Educators in Islam: A Study of Their Status, Roles, Duties, and Challenges from the Perspective of Islamic Education - Lalu Yusri Bahtiar; Syarifuddin Ondeng; Munawir Kamaluddin (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Education in Islam is not merely aimed at transferring knowledge, but also at shaping the character, morals, and spirituality of learners toward becoming a perfect human being (insan kamil). One of the key components that determines the success of such education is the educator. This study aims to examine the definition, position, duties and roles, characteristics, as well as challenges faced by educators from an Islamic perspective. This research employs a qualitative method using a library research approach, where data are collected through the review and analysis of literature such as books and scientific journals, as well as primary sources including the Quran and Hadith relevant to the theme of educators in Islam. The data are analyzed using content analysis through a descriptive-qualitative technique. The findings indicate that the term